Nexus - Miller, Henry, 1891-1980 (Miller, Henry, 1891-1980. Rosy crucifixion (New York, N.Y.), 1987)
The final novel of Miller's frank, autobiographical trilogy continues to use burlesque, fantasy and dream to portray the life of a struggling writer in pre-World War I New York.